Oxygen and air nanobubble water solution promote the growth of plants, fishes, and mice. - Kosuke Ebina; Kenrin Shi; Makoto Hirao; Jun Hashimoto; Yoshitaka Kawato; Shoichi Kaneshiro; Tokimitsu Morimoto; Kota Koizumi; Hideki Yoshikawa (PLoS ONE, 2013)
Nanobubbles (<200 nm in diameter) have several unique properties such as long lifetime in liquid owing to its negatively charged surface, and its high gas solubility into the liquid owing to its high internal pressure. They are used in variety of fields including diagnostic aids and drug delivery, while there are no reports assessing their effects on the growth of lives. Nanobubbles of air or oxygen gas were generated using a nanobubble aerator (BUVITAS; Ligaric Company Limited, Osaka, Japan). Brassica campestris were cultured hydroponically for 4 weeks within air-nanobubble water or within normal water. Sweetfish (for 3 weeks) and rainbow trout (for 6 weeks) were kept either within air-nanobubble water or within normal water. Finally, 5 week-old male DBA1/J mice were bred with normal free-chaw and free-drinking either of oxygen-nanobubble water or of normal water for 12 weeks. Oxygen-nanobubble significantly increased the dissolved oxygen concentration of water as well as concentration/size of nanobubbles which were relatively stable for 70 days. Air-nanobubble water significantly promoted the height (19.1 vs. 16.7 cm; P<0.05), length of leaves (24.4 vs. 22.4 cm; P<0.01), and aerial fresh weight (27.3 vs. 20.3 g; P<0.01) of Brassica campestris compared to normal water. Total weight of sweetfish increased from 3.0 to 6.4 kg in normal water, whereas it increased from 3.0 to 10.2 kg in air-nanobubble water. In addition, total weight of rainbow trout increased from 50.0 to 129.5 kg in normal water, whereas it increased from 50.0 to 148.0 kg in air-nanobubble water. Free oral intake of oxygen-nanobubble water significantly promoted the weight (23.5 vs. 21.8 g; P<0.01) and the length (17.0 vs. 16.1 cm; P<0.001) of mice compared to that of normal water. We have demonstrated for the first time that oxygen and air-nanobubble water may be potentially effective tools for the growth of lives.